Quando serve la psicoterapia: gli adolescenti e le dinamiche del gruppo - Del Bianco, Vilma (Il sogno della farfalla, 2007)
When facing the crisis of an adolescent, should we just let it pass, putting it down to physiological causes or should we intervene immediately and see it as a sign of something gone wrong? Are we simply dealing with turmoil or is it indicative of some form of pathology? These complex issues have so far received little attention from modern psychiatry which, in spite of appearances does not adequately offer a response to the urgency of these requests, preferring to sit back and wait given that these “adolescents” “undermine” the theoretical framework of psychotherapies. A different theory and methodology that envisage the presence of an “active” psychiatrist can allow us to respond to requests of help which are more or less explicit and, once a diagnosis has been made, offer a therapy and, in particular, a psychotherapy. Having established this premise and on the basis of the author’s clinical experience, the article goes about demonstrating that the group setting creates a greater therapeutic response, thanks to the fact that it reflects the lives of adolescents at a deeper level (peer groups, greater irrational dimensions...) There is an evident reduction of therapeutic abandonment characteristic of adolescence; and furthermore a number of elements among which the “obligation” to relate to others, the sharing of therapeutic work, and above all the irrational relationship that develops within the group, with dreams and interpretations, allow one to rediscover those possibilities that we thought lost, and the capacity to imagine that was feared thwarted forever.